JEAN BAUDRILLAD'S HYPERREAL: ANALYSIS OF THEME IN YOASOBI'S SONG "IDOL" - Muhammad Aghni Ismatuloh (British (Jurnal Bahasa dan Sastra Inggris), 2023)
Jean Baudrillard is one among many prominent thinkers of postmodernism. One among many his notable idea is the Hyperreal In his book Simulacra and Simulation, Baudrillard’s proposes the idea of something that transcend beyond the state of fake and reality, the Hyperreal. This concept can be found as a theme in lyrics of a song titled Idol by Yoasobi. This paper try to dissect the lyrics and finding the implication of Baudrillard’s concept of Hyperreal within the implicit and explicit meanings of the lyrics. Idol is a certain profession that has gain significant rise in the 21th century. The common perception is that they are selling ‘fake identities’ to their audience. Nevertheless, the truth is more complicated than it is as with using Baudrillard’s theoretical framework of the Hyperreal, idol has cross the boundary of falsehood and authenticity and become ‘real’ in their own sense.   Keywords: Baurillard, Hyperreal, Simulation, Idol, Seality